Health Journalism Internships: A Social Marketing Strategy to Address Health Disparities - Nguyen, Duy H. (Springer-Verlag, 2010)
The USA seeks to eliminate health disparities by stimulating the rapid uptake of health-promoting behaviors within disadvantaged communities. A health journalism internship incorporates social marketing strategies to increase communities' access to cancer information, while helping the interns who are recruited from underrepresented communities gain admission to top graduate schools. Interns are taught basic health journalism skills that enable them to create immediate streams of cancer-related press releases for submission to community newspapers. Interns are charged with the social responsibility of continuing this dissemination process throughout their careers. Intermediate outcomes are measured as mediators of distal behavioral change goals.